Proposing local trees diversity for rehabilitation of degraded lowland areas surrounding springs - SOEJONO SOEJONO; SUGENG BUDIHARTA; ENDANG ARISOESILANINGSIH (Society for Indonesian Biodiversity, 2013)
Soejono, Budiharta S, Arisoesilaningsih E. 2013. Proposing local trees diversity for rehabilitation of degraded lowland areasÂ surrounding water spring. Biodiversitas 14: 37-42. This study was aimed to propose alternative trees diversity for rehabilitation ofÂ degraded lowland area surrounding spring. Data were collected by vegetation analysis of three sampling sites (1st Gajahrejo, 2nd Cowek, 3rdÂ Parerejo)Â to determine density, frequency, dominancy, diversity index and Important Value Index (IVI). The lists of plants in threeÂ sites were then compiled into an integrated list and used as reference for developing questionnaire. The questionnaire was thenÂ distributed to respondents who were chosen randomly. We recorded their preferences of tree species in rehabilitation program based onÂ socio-economical and ecological aspects. Selected species were then proposed as alternative plants for rehabilitation of degraded springÂ area based on landscape topography and remaining vegetation coverage. The results showed that species diversity of Moraceae familyÂ was the highest than other families. In term of ecological aspect, Ficus racemosa, Artocarpus elasticus, Bambusa blumeana,Â Dendrocalamus asper, Gigantochloa atter, Ficus benjamina, Syzygium samarangense and Ficus virens showed high Important ValueÂ Index. On the other hand, based on socio-economic aspects, Ficus benjamina, Artocarpus elasticus, Artocarpus altilis, Artocarpus altilisÂ â€œSeedlessâ€, Durio zibethinus, Ficus drupacea, Pangium edule, Ficus variegata, Michelia champaca, Aleurites moluccana and FicusÂ racemosa were the most preferred species by local community. Based on topography and vegetation coverage, spring surrounding areasÂ were classified into four: steep and open, flat and open, steep and dense, and flat and dense. Therefore among of 120 species found in allÂ sampling sites, there were respectively 63.3%, 95%, 25% and 44.16% species to be proposed and planted for rehabilitation in the fourÂ classified areas.